2000
DOI: 10.1097/00007890-200007270-00018
|View full text |Cite
|
Sign up to set email alerts
|

Prolongation of Liver Allograft Survival After Interleukin-10 Gene Transduction 24???48 Hours Before Donation1

Abstract: The prolongation of survival of IL-10 cDNA transferred liver allografts might be due to inhibition of the early phase of alloimmune-response by over expression of IL-10, despite the expression of IL-2 and interferon-gamma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…The hepatoprotective effects of IL-10 most likely stem from its known effects in downregulation of proinflammatory cytokines, reduction of oxidative stress and modulation of other hepatoprotective molecular pathways (29,30). The known antiinflammatory and immunosuppressive effects of IL-10 may be responsible for the observed reduction in the risk of moderate and severe rejection in the IPC group (30,31). However, recent data show that a diagnosis of acute rejection is more common in HCV recipients in the first 6 months (32), and therefore, one cannot rule out the confounding effect caused by the greater number of recipients with HCV diagnosis in the No IPC group.…”
Section: Koneru Et Almentioning
confidence: 99%
“…The hepatoprotective effects of IL-10 most likely stem from its known effects in downregulation of proinflammatory cytokines, reduction of oxidative stress and modulation of other hepatoprotective molecular pathways (29,30). The known antiinflammatory and immunosuppressive effects of IL-10 may be responsible for the observed reduction in the risk of moderate and severe rejection in the IPC group (30,31). However, recent data show that a diagnosis of acute rejection is more common in HCV recipients in the first 6 months (32), and therefore, one cannot rule out the confounding effect caused by the greater number of recipients with HCV diagnosis in the No IPC group.…”
Section: Koneru Et Almentioning
confidence: 99%
“…52 Thus, it had been proposed that Th2 cytokines could inhibit transplant rejection by inhibiting Th1 cytokines that promote rejection. 53 Although there is some evidence that Th2 cytokines can prolong liver allograft survival because transfection of transplanted livers with IL-10 prolongs their survival, 54 the lack of correlation between cytokine expression and graft outcome make such concepts doubtful. 50,54,55 Human liver transplants similarly show poor correlation between Th1 or Th2 cytokine expression and the outcome of transplantation.…”
Section: Immune Activation Not Immune Deviation Is Associated With mentioning
confidence: 99%
“…53 Although there is some evidence that Th2 cytokines can prolong liver allograft survival because transfection of transplanted livers with IL-10 prolongs their survival, 54 the lack of correlation between cytokine expression and graft outcome make such concepts doubtful. 50,54,55 Human liver transplants similarly show poor correlation between Th1 or Th2 cytokine expression and the outcome of transplantation. 56,57 With the evidence that donor leukocytes were responsible for tolerance and that these cells migrated to recipient lymphoid tissue, examination of the cytokine response in lymphoid tissue rather than the allograft itself seemed warranted.…”
Section: Immune Activation Not Immune Deviation Is Associated With mentioning
confidence: 99%
“…The cells were grown at 37°C in 5% CO2. The MSCs used in all in-vivo experiments were maintained in passages [8][9][10][11].…”
Section: Cell Culturementioning
confidence: 99%
“…IL-10 was described originally as a cytokine synthesis inhibitory factor, which could down-regulate a variety of immune responses. Several lines of evidence have demonstrated that genetic delivery of IL-10 to allografts leads to improved graft acceptance in animal heart [10] or liver transplantation [11] models. Given that IL-10 is a cytokine synthesis inhibitory factor, we hypothesized that genetic delivery of IL-10 may confer measurable and perceptible beneficial effects in liver transplantation treatment.…”
Section: Introductionmentioning
confidence: 99%